Pengendalian Kecepatan Gerak Quadcopter Berbasis IMU pada Gerakan Tangan dengan Metode Template Matching - Nofria Hanafi; Abdul Mu'iz Miftahudin; Naufal Ali Akbar C; R. Sanggar Dewanto (Jurnal Rekayasa Elektrika, 2018)
An aerial vehicle has actuator four brushless DC motors (quadcopter) which is operated using a remote control or automatically. An aerial vehicle commonly called a quadcopter is controlled by using sensor data Inertia Measurement Unit (IMU) especially gyroscope and accelerometer sensor. Motion control is a stick control with sensor data IMU as data input. The motion from the aerial vehicle is a two-dimension (2D) motion from X axis and Y axis. Data sensor IMU is read by a microcontroller and will be processed to get real data acceleration (acceleration without influenced gravitation) remotely. The distance gesture inertia and the speed at which it operates are the parameter that is converted into an air vehicle motion. Trajectory motion is changed into picture domain 10x10 pixel as the comparison with the template matching algorithm. Match motion recognition is a motion command to the quadcopter. The simple motion like vertical, horizontal, diagonal, and curve match 96% using template matching algorithm and trajectory estimation.